Equality Analysis Of The Right Education For Disabilities: A Juridical And Factual Study Implementation Of Management Inclusion Education - Asep Sunandar; Ediyanto Ediyanto; Ade Dian Firdiana; Deni Hadiana; Muhammad Zidni Ilman Nafiah; Ni’matul Lailiyah; Thalsa Syahda Aqila; Siti Romlah; Sri Hadayani (Department of Special Education, 2022)
Education is a human right, everyone has the right to get educational services as a manifestation to achieve a better life. This study tries to analyze the guarantee of disability rights and inclusive school policies in a juridical and implementing way. Education guarantees for disabilities are contained in Law No. 8 of 2016 concerning Persons with Disabilities, Government Regulation No. 13 of 2020 concerning Adequate Accommodation for Students with Disabilities and Permendikbud No 70 of 2009 concerning Inclusive Education. Malang City has designated 57 public/private elementary schools, and 16 public/private junior high schools as inclusive schools. The City of Probolinggo has designated 16 public/private elementary schools and 6 public/private junior high schools as inclusive schools. The policies in these two areas are based on the principle that schools should not refuse students with disabilities, after a prospective student registers, the school prepares for inclusive classroom learning. The weakness of the implementation of inclusive education in these two areas is the unavailability of adequate learning facilities and the availability of qualified special assistant teachers. So that to achieve the success of inclusive education policies, it is necessary to support infrastructure and human resources of educators that match the educational background with the required competencies.